Neurological changes and outcomes of paediatric surgery of the aortic arch using selective cerebral perfusion - Raúl Sánchez Pérez; Pilar Tirado Requero; Luz Polo López; Juvenal Rey Lois; Bunty Ramchandani Ramchandani; Luis Guereta Silva; Álvaro González Rocafort; Ángel Aroca Peinado (Elsevier, 2020)
Introduction: The aims of this article are to analyse the neuropsychological changes in the medium-term in children subjected to aortic arch surgery using selective cerebral perfusion (SCP), as well as to detect any modifiable factors in the surgical technique that may contribute to minimising the subsequent neurological involvement. Material and methods: Inclusion criteria were established as: aortic arch disease operated on using SCP during the first year of life, between 10 August 2004 and 24 May 2016, biventricular physiology, and gestational age greater than 31 weeks. In the absence of a chromosomal disease, they were classified, from a neurological point of view, using the Rankin score. Children over 4-years of age were subjected to intelligence studies, including attention level, development, and psycho-lingual skills. Results: The study included a total of 82 patients with a mean age of 1.8 months. The mean SCP flow was 32 ml/kg/min. The mean time of SCP was 31 min. The overall mortality of the series was 14.8%. Neurological dysfunction was observed in 35.9% of patients, and the following were detected as risk factors: surgery in patients less than 10-days-old, duration of SCP greater than 40 min, and the time required for the cooling down and/or warming-up. Attention deficit was diagnosed in 35.2% of patients greater than 5-years-old. Conclusions: Patients operated on using SCP in in the first year of life required a neuropsychological follow-up, and there are modifiable surgical factors that may have an influence on neurological development. Resumen: Introducción: Los objetivos son analizar las alteraciones neuropsicológicas a medio plazo de los niños intervenidos del arco aórtico mediante perfusión cerebral selectiva (PCS) y detectar posibles factores modificables en la técnica quirúrgica que pueden ayudar a minimizar la afectación neurológica posterior. Material y métodos: Se establecieron como criterios de inclusión: patología del arco aórtico intervenida mediante PCS durante el primer año de vida, entre el 10 de Agosto de 2004 y el 24 de Mayo de 2016, fisiología biventricular y edad gestacional mayor de 31 semanas. En ausencia de cromosomopatía se clasificaron desde el punto de vista neurológico siguiendo el modified Rankin score. En mayores de 4 años se realizaron estudios de inteligencia, nivel de atención, maduración y aptitudes piscolingüisticas. Resultados: 82 pacientes se incluyeron, cuya edad media en el momento de la cirugía fue de 1,8 meses. El Flujo medio en PCS fue de 32 ml/kg/min. El tiempo medio de PCS fue de 31 minutos. La mortalidad global de la serie fue de 14,8 %. Con disfunción neurológica se observaron un 35,9 % y se detectaron como factores de riesgo: cirugía en menores de 10 días de edad, duración de PCS mayor de 40 minutos y la duración del enfriamiento y/o calentamiento. Un 35,2 % de los pacientes mayor de 5 años fueron diagnosticados de déficit de atención. Conclusiones: Los pacientes intervenidos en el primer año de vida con PCS precisan un seguimiento neuropsicológico y hay factores modificables quirúrgicos que pueden influir en el desarrollo neurológico.